2012
DOI: 10.1039/c2ob06904k
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic formal synthesis of (−)- and (+)-epibatidine

Abstract: The cis-dihydrocatechol, derived from enzymatic cis-dihydroxylation of bromobenzene using the microorganism Pseudomonas putida UV4, was converted into (-)-epibatidine in eleven steps with complete stereocontrol. In addition, an unprecedented palladium-catalysed disproportionation reaction gave the (+)-enantiomer of an advanced key intermediate employed in a previous synthesis of epibatidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Therefore, the possibility of forming and separating crystalline derivatives from azidoacetates 8c , 9c , 11c , and 12c , which might be suitable for X‐ray crystallography, and the resulting unequivocal determination of structure and relative stereochemistry, was also investigated. As part of our earlier unpublished efforts, to synthesize the alkaloid epibatidine from cis ‐diols 2b and 2c , attempts were made to characterize the products ( 8c , 9c , 11c , and 12c ) through the formation of their derivatives. In order to solve the problem of product equilibration, the azide groups present in compounds 8c , 9c , 11c , and 12c were reduced with trimethyl phosphine, using a Staudinger reaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the possibility of forming and separating crystalline derivatives from azidoacetates 8c , 9c , 11c , and 12c , which might be suitable for X‐ray crystallography, and the resulting unequivocal determination of structure and relative stereochemistry, was also investigated. As part of our earlier unpublished efforts, to synthesize the alkaloid epibatidine from cis ‐diols 2b and 2c , attempts were made to characterize the products ( 8c , 9c , 11c , and 12c ) through the formation of their derivatives. In order to solve the problem of product equilibration, the azide groups present in compounds 8c , 9c , 11c , and 12c were reduced with trimethyl phosphine, using a Staudinger reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The cooled mixture was diluted with EtOAc (100 mL) and washed with brine containing 2% NaOH (3 × 50 mL) and saturated NH 4 Cl solution (75 mL). The organic phase was dried (Na 2 SO 4 ) and concentrated under reduced pressure, and the residue was purified by flash chromatography (pentane:EtOAc gradient 90:10 → 40:60) to afford compound 19c (1.1 g, 84%) as a white needles; mp 152-153°C (from EtOAc) (lit., mp 135°C) [32] ; (27), 67 (11).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to the high fidelity of the [1,3]‐transfer of chirality, the [3,3]‐sigmatropic rearrangement proved to be a powerful tool in natural product synthesis. Stevenson et al reported the synthesis of (–)‐epibatidine with use of this rearrangement as key step for the introduction of the amino group (Scheme ) . Dehydration of carbamate 38 , obtained from 37 under Appel's conditions, gave the isocyanate 39 , which was treated with t BuOH to form the diene 40 , an advanced precursor of the desired natural product.…”
Section: Applications In Natural Products Synthesismentioning
confidence: 99%